Geger Sikep: Environmental (Re)Interpretation among the Contemporary Anti-Cement Movement in Kendeng, Central Java - Setiadi, Setiadi; Saraswati, Aprilia Rejeki; Rosyid, Nur (Universitas Negeri Semarang, 2017)
Over the past decade, a shift has occurred in the Sedulur Sikep community’s attitude since the increase in its popularity and coverage in the mass media following its involvement in the anti-cement movement in Central Java. However, not all members of Sedulur Sikep participate in or even approve of this movement. This anthropological study attempts to illustrate how this situation has pushed the Sikep community members to (re)recognize their values, the influence of these values on environmental discourse, and how the relations between them are understood and practiced by Sedulur Sikep and the movement fighting in its name. By examining the adaptability of ecological knowledge and the ordering of visible space as a result of complex interactions between nature and nurture, it is possible to examine the shifts in their understanding of environmental dynamics and their cultural identity. The ‘fragmentation’ that has occurred is rooted in different understandings of the reciprocal bonds between the Sedulur Sikep’s tani mligi identity and natural resources. The dynamics and stagnation seen in how Sedulur Sikep positions itself in relation to cement production is also apparent in various methods of (re)interpretation, particularly regarding the relevance of Sedulur Sikep’s beliefs to its ecological contestation and struggle for living space.